READING ONLINE: EVALUATION OF ONLINE SOURCES CREDIBILITY - Fatimah Tuzahra (Universitas Teknokrat Indonesia, 2021)
The vast amount of online information demands readers to check its credibility since fabricated information has widely been misused and also supported by a lack of filters in web-based sources in ensuring its quality. In practice, checking the credibility of an online source is not an easy task to do as searchers need to consider several aspects in its application. This happens due to some factors, such as language and searchers’ willingness in identifying the quality of online information. This paper focuses on the evaluation of online sources' credibility covering scholars’ definitions of online sources credibility, English-native and foreign searchers’ perspective in judging online sources, and varied criteria applied in online sources credibility in which give insight for readers about this issue and provide references for further study.